FINANCIAL ASSESSMENT OF PROJECT SUSTAINABILITY USING ALTMAN Z-SCORE MODEL (CASE STUDY PT. DIRGANTARA INDONESIA Aerospace) - Tiaranita - Nim: 29115611 , Rizella
The demand for aircraft product is increasing and lead to production for making new aircraft should increase too. PT. DI as one aircraft manufacturing company go through the fact that the sales from aircraft and profit of the company were declining and make concern to company sustainability in the future. The financial assessment will analyze using financial ratio, growth rate, Altman Z-sore model, and sensitivity analysis. The result from the financial ratio calculation showed that the company did not perform a good financial performance. Based on calculation growth rate showed that company needed the external fund for sustainable growth. The z-score value used to predict the probability of a company will go into bankruptcy or not. The z-score value of PT. DI in 2016 is 1.92 (grey zone) that mean that company has financial difficulties, but are saved and possibly bankrupt depends on the decision of the companyÃ‚Â’s management policy as a decision maker. Sensitivity analysis used to increasing value each variable into the safe zone and resulted that company should increase 32% for each variable in Altman formula within simultaneously. This increasing expected to lead PT. DI in the safe zone, and affected for the future sustainability company.